KAJIAN SUBSTITUSI TEPUNG TERIGU DENGAN MAIZENA PADA PEMBUATAN SOSIS SAPI RENDAH LEMAK (Low Fat Beef Sausage) - Budianta, Tarsisius Dwi Wibawa; Srianta, Ign.; Natria, Ursula Angelika (Widya Mandala Surabaya Catholic University, 2004)
Sausage is chopped and seasoned meat product with high nutritional value. Sausage was usually made of animal fat, but many people prefer to avoid too much animal fat consumption. This present research, beef sausage was made of corn oil (it was called low fat beef sausage. The aim of the research was to determine the effect of the substitution of wheat flour with maize on the physichochemical and sensory properties and to find the best proportion of wheat flour substitution. Block Randomized Design with single factor, i.e. the proportion of wheat flour and maize (3%: 0; 2,5%:0,5%; 2%:1%; 1,5%:1,5%; 1%:2%; 0,5%:2,5%; 0:3%) was used. The result of this research showed that wheat flour substitution with maize increased moisture and fat content, but decreased the protein content of the sausage. The substitution also increased juiciness, compactness, hardness and cohesiveness of the low fat beef sausage. Substitution of wheat flour at the proportion of wheat flour and maize 1.5%:1.5% resulted in the best properties of low fat beef sausage.